Harmful Adulterants in Seized Amphetamine Tablets in Iraq: Profiling and Health Risks - Duaa Ahmed Akhmais,; Noor Sabah,; Zainab Khalid Ali,; Zainab Karim Jaffar, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Amphetamine type stimulants (ATS) refers to a class of drugs that are primarily synthetic and that stimulate the central nervous system. When overdosed or abused over an extended period of time can lead to psychotic toxicity, reduce fatigue, and increase wakefulness and activity levels, has been adulterated with various substances in illicit markets. Adulterants that raise the possibility of harm include caffeine, lidocaine, diphenhydramine, quinin and others, these substances are likely used to enhance the stimulant effects, reduce cardiovascular side effects, or mitigate symptoms like insomnia. However, the presence of these additives heightens the risk of toxicity and adverse health effects These findings underscore the significant health risks posed by adulterants in amphetamine tablets, calling for stronger measures to prevent illegal distribution and increase public awareness. Objectives: This study investigates amphetamine tablets seized in Iraq to identify the presence of these adulterants and assess their harmful impact. It also intends to increase public awareness of the health dangers associated with drug adulterants. Method: Amphetamine tablets were secretly gathered from various seizures to protect privacy and safety in the forensic medicine department. The tablets were then examined using GC-MS to detect the presence of adulterants and amphetamine. Expected outcomes: A statistical study will be conducted to determine the prevalence of different adulterants, identify frequent adulterants recognized with amphetamine, and examine the health concerns associated with these adulterants. Conclusion: An addiction on amphetamine can result in serious medical risks such as heart problems, psychological disorders like anxiety and cognitive impairment, adulterated amphetamine which increases the risk of unpredictable, toxic reactions, making it even more dangerous so reducing or stopping use ensure access to treatment are crucial to prevent health damage.